ANALYSIS OF WORK PROGRAM MEASUREMENT, APPARATUS DISCIPLINE, AND LEADERSHIP STYLE IN ORDER TO MAXIMIZE VILLAGE FINANCIAL MANAGEMENT PERFORMANCE IN ACEH PROVINCE - Wahyuddin Albra (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2025)
This study aims to analyze the influence of work program measurement, apparatus discipline, and leadership style on the performance of village financial management in Aceh Province. Effective and accountable village financial management has become a crucial requirement along with the increasing allocation of Village Funds from the central government. However, in practice, various problems are still found related to the planning, implementation, and accountability of village finances. This study uses a quantitative approach with an associative research design. Data were obtained by distributing questionnaires to village officials directly involved in village financial management in Aceh Province. Data analysis techniques used include validity testing, reliability testing, descriptive statistical analysis, and multiple linear regression analysis to examine the influence between research variables. The results show that work program measurement, apparatus discipline, and leadership style have a positive and significant effect on the performance of village financial management. Among these three variables, the village head's leadership style has the most dominant influence. This finding indicates that effective leadership can encourage village officials to work more disciplined and implement work programs optimally. This study provides a theoretical contribution to the development of public administration studies, particularly related to village financial management. Practically, the results of this study are expected to be a basis for village governments and regional governments in formulating policies and strategies to improve the performance of village financial management in Aceh Province.